Tecnologia de produção de kombucha e seus benefícios para a saúde - Schedenffeldt, Beatriz Ferrari (Universidade Federal de São Carlos, 2024)
Kombucha is a beverage obtained through the fermentation of tea from the Camellia sinensis plant, sugar, and a culture of bacteria and yeast known as SCOBY. The consumption of this functional drink has significantly increased in recent years due to a growing demand for foods with health-benefiting properties, as people seek a healthier lifestyle. This study aims to conduct a literature review on the chemical and microbial composition of kombucha, potential production technologies for this fermented beverage, its health benefits, while also evaluating technological innovations and current market trends for kombuchas in Brazil. Upon analysis of the studies, it was found that kombucha's chemical composition is rich in organic compounds, resulting in antioxidant and antimicrobial effects, and a reduction in health-related issues, such as cancer prevention, arthritis relief, improved immunity, anti-hypertensive activity, anticholesterolemic effects, and anti-inflammatory properties. The beverage's symbiotic culture can act in the human body with a probiotic effect. Kombucha can be produced either artisanally or on an industrial scale, depending on the available infrastructure for its production. The basic steps include: preparation of infused tea, first fermentation in aerobic conditions, flavoring and carbonation in suitable bottles or cans, and the second fermentation in anaerobic conditions. In conclusion, due to its significant growth potential, further studies will be conducted to analyze the benefits of the drink and develop new formulations and processing alterations.
Kombucha production technology and its health benefits
Keywords: Alimentos funcionais; Bebida fermentada; Camellia sinensis; Functional foods; Fermented beverage; Camellia sinensis; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS